Influência do sexo na resposta inflamatória ao LPS de células micróglia-símile derivadas de monócitos de pacientes com esquizofrenia - Cordeiro, Rafaela Carneiro (2021)
Schizophrenia is one of the most complex and poorly understood psychiatric disorders, due to its heterogeneity of clinical presentation, which can lead to a progressive functional decline of the patient that impacts the cognitive, affective, and social domains, as well as the multiplicity of genetic and environmental risk factors in its pathophysiology. Findings point to the neurodevelopmental nature of schizophrenia, as well as an influence of biological sex, with men presenting early disease-onset and more severe symptoms such as negative and cognitive symptoms. Epidemiological studies indicate a role of inflammation in its pathophysiology, with probable involvement of microglia, resident immune cells of the brain. To date, most human microglia research has been conducted using post-mortem brain or PET scan, however it is difficult to determine molecular pathological mechanisms such as the signaling pathway and pattern of gene expression. Therefore, human studies using live brain cells derived from psychiatric patients are warranted to assess the interactions of microglial activity and deeper psychopathology, including psychiatric symptoms. Thus, in the present study, we investigated the expression of inflammatory factors in microglia after stimulation with lipopolysaccharide (LPS), using induced microglia-like cells (iMG) from monocytes derived from 12 patients and 12 controls, half of each sex. Subsequently, the influence of the iMG response on a healthy control astrocyte lineage was evaluated. The expression of messenger RNA (mRNA) of factors known to be involved in inflammatory processes was quantified, such as pro- and antiinflammatory cytokines and components of the complement system, and molecules with possible neuroprotective activity, such as progranulin (GRN) and G protein associated estrogen receptor (GPER). The results show that iMGs derived from men and women with schizophrenia have different profiles of inflammatory response after stimulation with LPS, however cells derived from men with the disorder have higher levels of pro-inflammatory cytokines and lower basal levels of GRN and GPER molecules. with potential neuroprotective activity. In addition, this response influences the expression of GRN and CX3CL1 in astrocytes. Taken together, these data help explain the greater functional decline and greater manifestation of inflammatory changes in schizophrenia in males compared to females, an important step towards deciphering the specifics of schizophrenia pathophysiology.